2018
DOI: 10.1080/15389588.2018.1471599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the influence of road lighting on traffic safety at accesses using an artificial neural network

Abstract: Improved illuminance can decrease the speed variation among vehicles and improve safety levels. In addition, high-grade roads need better illuminance at accesses. A threshold value can also be obtained based on related variables and used to develop scientific guidelines for traffic management organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…23,24 The lighting effect is especially obvious on high-speed roads or roads with many lanes. 25 Wanvik 26 found that road lighting can reduce night-time injuries by 50% based on an interactive database of 763,000 injuries and 3.3 million property loss incidents from 1987 to 2006. The probability of night-time vehicle accidents also differs among different types of roads.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The lighting effect is especially obvious on high-speed roads or roads with many lanes. 25 Wanvik 26 found that road lighting can reduce night-time injuries by 50% based on an interactive database of 763,000 injuries and 3.3 million property loss incidents from 1987 to 2006. The probability of night-time vehicle accidents also differs among different types of roads.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the correlations between nighttime light and socioeconomical indices. However, previous studies have mainly employed nighttime light data to model socioeconomic phenomena, such as urban expansion [14], economic development [23], energy consumption [24], population density [25] and transportation mobility [26], and there has been a lack of studies that coupled nighttime light images and socioeconomic data to comprehensively explore the driving factors of artificial lighting changes. This study employed the driving factors according to different city groups distinguished by differences in urban economy, population density, geographical location, and industrial structure.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that socioeconomic parameters, such as population [25,31,32], economy [33,34], transportation [26], and electricity consumption [23,24], are related to nighttime lighting. This study couples the socioeconomic data and nighttime light images to explore the driving factors of urban artificial lighting change.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of the IoT with intelligent traffic systems has recently been explored [1,2,3,4,5]. The IoT can provide both infrastructure and vehicles with sensors that can measure general traffic conditions, ambient variables, vehicle variables (such as position and speed), and driver conditions.…”
Section: Introductionmentioning
confidence: 99%